Ulcerative balanoposthitis associated with non-syphilitic spirochaetal infection. Issue 1 (February 1986) - Piot, P; Duncan, M; Van Dyck, E; Ballard, R C
Abstract : Ulcerative balanoposthitis associated with non-syphilitic spirochaetal infection was found in 41 (12%) of 344 consecutive men with genital ulcer disease in two clinics in South Africa. All patients with non-syphilitic spirochaetal infection were uncircumcised. Non-syphilitic treponemes were seen in only two of 60 uncircumcised men who had urethritis without genital ulceration. In 14 patients with ulcerative balanoposthitis no cause of genital ulceration could be identified. Most patients presented with large, serpiginous, superficial, foul smelling, and tender ulcers, the base of which was purulent with undermined edges. Non-tender inguinal lymphadenopathy was present in seven of 14 patients. One female sexual partner of a patient with non-syphilitic spirochaetal infection had a vaginal infection with non-syphilitic spirochaetes.